2010
DOI: 10.1038/cdd.2010.16
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase-1 regulates Akt1 signal transduction pathway to control gene expression, cell survival and differentiation

Abstract: AKT pathway has a critical role in mediating signaling transductions for cell proliferation, differentiation and survival. Previous studies have shown that AKT activation is achieved through a series of phosphorylation steps: first, AKT is phosphorylated at Thr-450 by JNK kinases to prime its activation; then, phosphoinositide-dependent kinase 1 phosphorylates AKT at Thr-308 to expose the Ser-473 residue; and finally, AKT is phosphorylated at Ser-473 by several kinases (PKD2 and others) to achieve its full act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 62 publications
4
84
0
2
Order By: Relevance
“…PP-1 is a major phosphatase that can directly dephosphorylate proteins, such as AKT, to modulate their activation and regulate the expression of downstream genes. It may be related with the inhibitory effect of heparin on tumor growth as other studies have reported; PP-1 can promote cell survival and modulate cell differentiation (Xiao et al, 2010). TGF-␤ has profound effects on all cell types that comprise the vasculature, including endothelial cells.…”
Section: Discussionmentioning
confidence: 94%
“…PP-1 is a major phosphatase that can directly dephosphorylate proteins, such as AKT, to modulate their activation and regulate the expression of downstream genes. It may be related with the inhibitory effect of heparin on tumor growth as other studies have reported; PP-1 can promote cell survival and modulate cell differentiation (Xiao et al, 2010). TGF-␤ has profound effects on all cell types that comprise the vasculature, including endothelial cells.…”
Section: Discussionmentioning
confidence: 94%
“…S1C). A thorough analysis of Pax-6 in four human ocular cell lines (20,21) revealed that p46, p43, and p32 were all present in these cells (Fig. S1D).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained with PC3 cells where the inhibition of invasion was 44, 64 and 87% for ASAH1, Akt2 and ASAH1 + Akt2, pro-apoptotic roles via dephosphorylating RB, [53][54][55] Bad, 56 Bax, 57 caspase-9 58 and T450 in Akt. 59 Therefore, inhibition of both Akt and ASAH1 would be predicted to result in maximal dephosphorylation of key regulators of the malignant phenotype.…”
Section: Resultsmentioning
confidence: 99%